1996
DOI: 10.1111/j.1600-0536.1996.tb02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical data on occupational contact urticaria

Abstract: Data on occupational contact urticaria (protein contact dermatitis included) in Finland during 1990-1994 were analyzed. Altogether 815 cases were reported to the Finnish Register of Occupational Diseases during this period, compared with 1944 cases of occupational allergic contact dermatitis. Accordingly, the total number of occupational allergic contact dermatoses was 2759, 29.5% being contact urticaria and 70.5% being allergic contact dermatitis. Occupational contact urticaria was much more common in women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 25 publications
4
60
1
2
Order By: Relevance
“…According to Finnish studies, farmers have demonstrated the highest prevalence of occupational contact urticaria [Kanerva et al, 1996], and dairy farming has been found to be an occupational risk factor for hand dermatoses [Susitaival et al, 1994[Susitaival et al, , 1995. Among private farmers in Poland, allergic contact dermatitis was the most common occupational dermatitis [Spiewak, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…According to Finnish studies, farmers have demonstrated the highest prevalence of occupational contact urticaria [Kanerva et al, 1996], and dairy farming has been found to be an occupational risk factor for hand dermatoses [Susitaival et al, 1994[Susitaival et al, , 1995. Among private farmers in Poland, allergic contact dermatitis was the most common occupational dermatitis [Spiewak, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been reported that the incidence of contact dermatitis to methacrylate resins in dental personnel is increasing due to the increased use of methacrylate containing materials (compomers, composites, RMGICs) to replace amalgam as a restorative material, especially in Europe. 20 The timescale of the ARRP is still too short to confirm this. The symptoms reported to the ARRP include dry, cracked, flaking skin on the hands and often fingertips with itching, irritation and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Intense, and sometimes irrelevant, discussions regarding the possible harmful effects of mercury in dental amalgam, has led to the decrease in mercury use in many countries, increasing the use of alternative products. 20,21 However, published research 22 also found that the incidence of oral lichenoid reactions adjacent to amalgam restorations occurred more often than other long-term side effects to dental materials. In addition, despite a reduction in dental caries in younger people 23 and an increase in the number of older people with their own teeth, this has not reduced the need for restorative dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly afected professional groups are healthcare employees, food handlers, farmers and hairdressers [24,25]. Immunologic and non-immunologic contact urticaria types can be seen in OCU.…”
Section: Occupational Contact Urticariamentioning
confidence: 99%